Education in a post Covid-19 scenario: how artificial intelligence has changed e-learning in the meta era - Kouveliotis, Kyriakos (Organizational corruption, crime and COVID-19, 2025)
The world is changing at an incredible rate, and different processes are using technology more and more every day. The education sector has also experienced tremendous technological changes during the post Covid-19 era. One of the most widely used applications of artificial intelligence today is to simplify employee tasks and office automation. In the future, robots will, like an author, be able to produce articles or create conferences and instructional videos. The more intelligent AI becomes, the more advanced the new education system will be. In such times, the educational method for each person may be different depending on their situation. The speed of teaching and learning, interaction with the teacher, and reaching answers in the intelligent education system increases. Artificial intelligence provides a variety of facilities for students with different physical problems. An increasing use of the latest technology advances in teaching students will accelerate their growth and progress and gives them the ability to confront the challenges of the ever-competitive world. After the Covid-19, both teachers and learners have been educated to a new understanding of technology use, which means that strategies for coping with real-world restrictions (such as the time limitations witnessed due to this pandemic and quarantine) are becoming more and more practical with technological applications. This chapter traces the changing education scenario, particularly e-learning, with the application of artificial intelligence.